Isolation of Entomopathogenic Nematodes (Steinernematidae and Heterorhabditidae) from Korea - Choo, Ho Yul (1995)
A survey for entomopathogenic nematodes was conducted throughout the nine provinces and within three city limits in the Republic of Korea during the summers of 1990 and 1991. Six of the nine provinces and one of the three cities were positive for entomopathogenic nematodes. Out of the total 499 soil samples, 23 (4.6%) were positive for entomopathogenic nematodes with 19 (3.8%) containing Steinernema and 4 (0.8%) containing Heterorhabditis. Heterorhabditis bacteriophora and three distinct groups of Steinernema species were identified. One of the three steinernematid groups was identified as S. carpocapsae based on cross breeding studies. Positive sample sites in each habitat included 15 of the 415 (3.6%) from forests including regrowth areas with shrubs, 1 of the 27 (3.7%) from turfgrass including golf courses and parks, 3 of the 24 (12.5%) from agricultural fields, 2 of the 16 (12.5%) along riparian areas, and 2 of the 17 (11.8%) near the seashore. We advocate that more surveys be conducted for entomopathogenic nematodes before commercial sources of nematodes are widely applied which may obscure the naturally-occurring nematodes.